Olga Tokarczuk’s art of reading: a linguistic view - Bilut-Homplewicz, Zofia; Krauz, Maria (Penerbit Universiti Kebangsaan Malaysia, 2024)
The purpose of this article is to analyze the process of reading shown from different perspectives in Olga Tokarczuk's essay Palec w soli, czyli Krótka historia mojego czytania (A Finger in the Salt, or A Short History of My Reading). The authors examine how the writer understands the process of reading, how she captures the category of the reader, and what role the imagination of the recipient plays in this process. They seek answers to questions such as what the history of the Nobel laureate’s reading is, how she describes the process considered “the miracle of reading,” and which literary works shaped her as a reader, a writer, or a person who discovers successive layers of the world through reading. The article portrays reading as an interweaving of primordial dichotomies: reading as a skill and process in human development versus reading as a process in the life of a writer; and of secondary dichotomies involving different criteria: age, gender, text type, and reader. As a result of the use of lexical-stylistic instrumentation, linguistic means of expression that sometimes form surprising combinations have been analyzed, making the text appear, to use a metaphor, as a kind of mosaic composed of different words and meanings that form a coherent and stimulating whole. The analysis shows that the mosaic character of the text manifests at its various levels. Olga Tokarczuk speaks about reading in scientific, popular and erudite language, with idiolectal elements and those belonging to the emotional register of everyday language. The distinction of unusual, even surprising collocation combinations and metaphors is an expression of the writer's creativity.